2013
DOI: 10.1039/c3sc50329a
|View full text |Cite
|
Sign up to set email alerts
|

A radical-based approach for the construction of the tetracyclic structure of resiniferatoxin

Abstract: A novel radical-based strategy for accessing the unique tetracyclic skeleton of resiniferatoxin is described. The synthetic route is characterized by a stereoselective synthesis of the C-ring which has a bridgehead O,Se-acetal, a three component radical coupling of the A-and C-rings and a branched allyl stannane, and a 7-endo radical cyclization to construct the fused B-ring from the coupling adduct. The present approach attests to the power of radical reactions to realize the congested C-C bond formations req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

4
6

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 65 publications
0
18
0
Order By: Relevance
“…Employing allylSnBu 3 (10 equiv) as nucleophile, this one-pot procedure provided a mixture of 9 and 10 in an unsatisfactory 1:2 ratio. 28 …”
Section: Resultsmentioning
confidence: 99%
“…Employing allylSnBu 3 (10 equiv) as nucleophile, this one-pot procedure provided a mixture of 9 and 10 in an unsatisfactory 1:2 ratio. 28 …”
Section: Resultsmentioning
confidence: 99%
“…Upon activation with CSA, the axial C9 alcohol of 11 participated in acetal exchange with the C13′ dimethyl acetal to provide the oxabicyclo[2.2.2]octane 12 (d.r.=1:1 at C13′). The C9 O,Se‐acetal was then constructed by conversion of the C9 vinyl ether of 12 8j. Thus, the vinyl ether 12 was chemoselectively oxidized by m CPBA to the carboxylic acid 13 via the intermediacy of the hydroxy ketone.…”
Section: Methodsmentioning
confidence: 99%
“…10a and V-40 (0.2 eq) were added by syringe pump over 3 h, and the reaction mixture was stirred for an additional 1 h. b) Compound 8e was obtained as a single diastereoisomer. 71) We demonstrated that the radical-mediated three-component reactions effectively incorporated the two carbocycles and a carbon chain into the multiply functionalized compounds. Thus, we planned to integrate the three-component reaction as a key assembling reaction of the A-and C-rings of resiniferatoxin (1).…”
Section: Radical-mediated Three-component Reactionmentioning
confidence: 99%